Design Innovation of a Solar-Powered Seawater Purification Device to Support Science Learning in Coastal Areas - Mitri Irianti; Ernidawati; Wilda Novianti; Zuhdi Ma’ruf; Zulhelmi; Naila Fauza; Idris; Abdul Hamid Sinaga; Rahmi Hidayah; Dhuha Fatihul Burhan (Jurnal Penelitian Pendidikan IPA, 2025)
Coastal communities in Indonesia face limited access to clean water because water sources are dominated by seawater and the availability of fresh water is extremely limited. This problem creates a need for innovative and sustainable solutions that can be applied in everyday life and utilized in science learning. This study aims to design and test the feasibility of a solar panel–based seawater purifier as a contextual physics learning medium and a means of providing clean water for coastal communities. The research method used is Research and Development (R&D), conducted through the stages of needs analysis, design, prototyping, expert validation, and limited field trials. Data collected includes expert validation results, practicality assessments by teachers and students, and empirical measurements of water quality such as pH, TDS, salinity, specific gravity, ORP, and EC. Qualitative findings from the validators indicate that this tool has good functionality, is relevant for learning, is easy to use, and is safe to operate. The results show an average validity of 3.73 (very valid) and practicality of 3.60 from students and 3.86 from teachers (very practical category). Water quality tests showed a pH of 6.83, TDS of 124 ppm, which meets WHO standards (TDS < 500 ppm), salinity of 0.01%, specific gravity (SG) of 1.00, ORP of 224 mV, and EC of 0 µS/cm, indicating that the water is suitable for consumption. Thus, the aim of the research is to produce a valid, practical seawater purifier and provide a sustainable alternative solution for the clean water needs of coastal communities.